Improving the airport operation and environmental quality at small airports in indonesia - Adisasmita, Sakti Adji; Hadipramana, Josef (International Journal of Sustainable Construction Engineering and Technology, 2011)
The study purpose is to strengthen the policy and supervision of airport operation and improve the airport environmental quality to face Green Airport in the near future. The data used are primary and secondary data. The primary data is based on field survey, interview and questionnaires, while secondary data is based on data collected from various agencies. In general, the conclusions are as follows: i) the study results show that the airport operator has given enough attention to the environmental management. With good environmental management, airport operator will find comfort in operating the airport such that airports could improve the operation and environmental quality control system; ii) the concept of green airport can be a reference to the the airport operator such that the airport activities does not negatively impact to the environment; and iii) the implementation of Green Airport concept will improve the quality of environment; and iv) the application of green airport concept will reduce the costs of environmental management. The recommendations are i) improve strategy and airport development in facing the green airport for the future challenges; and ii) airport development plan should noticed since the beginning of airport planned/developed so as to facilitate for the availability airport land expansion, permits, changes in traffic patterns, aircraft technology and implementation of environmental management aspect.